The Trado-Religious Worldview of Baranzan People: An Ethnogarhy of the Bajju in the Middle Belt of Nigeria - Luka Amos Yabo; Martin George (Perichoresis: The Theological Journal of Emanuel University)
This paper explores and evaluates the Trado-Religious Worldview of the Bajju, a tribal group in the middle belt of Nigeria. The study reveals the historicity and worldview of the Bajju people, who were traditionally horticulturalists and hunters, valuing large families. The research delves into the socio-cultural structure of the Bajju, their traditional beliefs, and their contemporary religious context. By utilizing data from questionnaires and emic experiences, the paper provides insight into the unique cultural and traditional heritage of the Bajju people in their milieu. The findings shed light on the Bajju culture, including leadership, relationships, marriage, family, social activities, kinship, and religion, offering a comprehensive understanding of this indigenous tribe in Nigeria.